SIGNIFICANCE ROLE OF TVET FOR DEVELOPING COUNTRY: STUDY ON BANGLADESH PERSPECTIVE - Ullah, Azmat; Parveen, Farnaz (International Journal of Research -GRANTHAALAYAH, 2018)
This paper emphasis on the role of Technical Vocational Education and Training (TVET) in development of our traditional education system into technical vocational education and training aspects in Bangladesh. The analysis in this paper reveals the limitations and opportunities of TVET in Bangladesh and provides recommendations for further enhancement of this concept application. The research has also addressed the need for an organized review of TVET in Bangladesh and its implications.